Characteristics of motives for the use of electronic social networks by students with different indicators of communication competency - Tkachov, Ivan V. (Journal of the Belarusian State University. Philosophy and Psychology, 2023)
The article examines the differences in the intensity of motives for the use of electronic social networks by students with different indicators of communication competency. The hypothesis of the study was the assumption that students with high and low indicators of communication competency have stronger motives for using electronic social networks, which are based on social needs, than students with medium indicators of competency. To diagnose the phenomena under study, offline questionnaires were administered at four Belarusian universities (n = 488). It was found that students with average communication competency indicators have the strongest motives for using electronic social networks. The obtained results contribute to the understanding of the role of students’ communication competency in motivating the use of electronic social networks and can be used for the development of teaching materials on the topics of digital communication, as well as for psychological correction of problematic use of electronic social networks.
Keywords: competency; communication competency; electronic social networks; motives for using electronic social networks; social intelligence; emotional intelligence; affiliation motive; students